2003
DOI: 10.1074/jbc.m303136200
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin K2 Regulation of Bone Homeostasis Is Mediated by the Steroid and Xenobiotic Receptor SXR

Abstract: Vitamin K 2 is a critical nutrient required for blood clotting that also plays an important role in bone formation. Vitamin K 2 supplementation up-regulates the expression of bone markers, increases bone density in vivo, and is used clinically in the management of osteoporosis. The mechanism of vitamin K 2 action in bone formation was thought to involve its normal role as an essential cofactor for ␥-carboxylation of bone matrix proteins. However, there is evidence that suggests vitamin K 2 also has a transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
258
1
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 338 publications
(279 citation statements)
references
References 71 publications
7
258
1
2
Order By: Relevance
“…Regulation of bone formation by vitamin K 2 may involve the γ-carboxylation of osteocalcin or may be mediated via the steroid and xenobiotic receptor (SXR) [13,27,[34][35][36]. However, it has also been reported that vitamin K 2 inhibits bone resorption via a mechanism that is independent of γ-carboxylation and related to its side chain [11].…”
Section: Introductionmentioning
confidence: 99%
“…Regulation of bone formation by vitamin K 2 may involve the γ-carboxylation of osteocalcin or may be mediated via the steroid and xenobiotic receptor (SXR) [13,27,[34][35][36]. However, it has also been reported that vitamin K 2 inhibits bone resorption via a mechanism that is independent of γ-carboxylation and related to its side chain [11].…”
Section: Introductionmentioning
confidence: 99%
“…The role of TERE1 in vitamin K-2, menaquinone, synthesis (Nakagawa et al, 2010) provides a highly probable and established mechanism of TERE1-mediated cholesterol modulation. Menaquinone is a known ligand for the nuclear receptor SXR (Tabb et al, 2003;Shearer and Newman, 2008;Zhou et al, 2009). SXR is known to heterodimerize with RXR and cross regulate LXR target genes that have wellestablished roles in modulation of cellular cholesterol efflux (Landes et al, 2003;Sonoda et al, 2005;Wang and Rader, 2007;Wang et al, , 2008bLim and Huang, 2008;Brown and Jessup, 2009;Zhou et al, 2009).…”
Section: Tere1 Modulation Of Cholesterolmentioning
confidence: 99%
“…In feeding studies Spronk et al (16) showed that MK4 but not vitamin K 1 could prevent arterial calcification in rats when given in combination with warfarin. Certain combinations of vitamin K and warfarin given to rodents have been shown to inhibit vitamin K-dependent γ-carboxylation in extrahepatic tissues but not in the liver which maintains a normal coagulation system (18). As reduced vitamin K 1 and reduced MK4 are both cofactors in the γ-carboxylation system, this finding has raised questions about additional effects of MK4 in the arterial wall which may enhance inhibition of arterial calcification.…”
mentioning
confidence: 99%